Hubungan Pengetahuan Ibu Terhadap Tindak Kekerasan Psikis Pada Anak - Ina Herlina; Masluroh Masluroh (Journal of Pharmaceutical and Health Research, 2023)
Cases of violence against women and children in Karawang Regency are still relatively high compared to the previous 3 years. The purpose of this study was to determine the relationship between mother's knowledge of acts of psychic violence in children, frequency distribution of mother's knowledge of acts of violence in children and frequency distribution of acts of psychic violence in children at the Tanjungpura Health Center in 2022. The type of research used in this study was quantitative research using the method Cross sectional by way of approach or data collection at one time only. The results showed that the mother's knowledge of acts of psychological violence in children was dominant in the good category, meaning that parents or mothers had good knowledge of acts of psychological violence in children. Where the results of the level of knowledge of the mother with a Good value of 79%, and Less 21%, the act of psychological violence committed by parents or mothers against children is low where it is found that those who do not do it are more dominant than those who do, namely as many as 85 people (85%) ,and those who committed acts of violence were 15 people (15%). There is an influence on the level of knowledge of mothers on psychological violence and the impact it has on children with a percentage (79%). There is no effect on the level of knowledge of mothers on psychological violence and the impact it has on children with a percentage (21%).